Numerical analysis for optimizing the determination of dynamic friction coefficient. (March 2016) - Jankowiak, T.; Rusinek, A.; List, G.; Sutter, G.; Abed, F.
Abstract: A proper definition of the real dynamic contact behavior is very important in numerical simulation of different dynamic processes such as machining, high speed cutting, impact and perforation of structures. This paper presents an optimal analysis for accurate estimation of the dynamic friction coefficient using a tribometer device. A three-dimensional finite element (FE) model is developed to better understand the test set-up and its associated method to accurately define the friction coefficient under dynamic loading. The aspect of the experimental methodology currently used to define the dynamic friction law and its main drawbacks are identified and discussed. Based on the FE analysis, a new methodology is proposed to estimate the dynamic friction by introducing the concept of a correction factor that can be used to correct the old experimental data. This correction factor depends on the initial projectile velocity and pressure for any friction coefficient value. Highlights: A numerical analysis is proposed to estimate dynamic friction coefficient accurately. A new method is developed to estimate local measurements not possible in experiments. A correction factor is introduced to correlate the experimental results. Effect of normal pressure and sliding velocity on dynamic friction is investigated.